Strengthening Religious Moderation through the Role of Civics Teachers - Mustafa, Mustafa (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
MAN Model Manado was the most prominent Islamic school in North Sulawesi Province. The student body of more than 1.400 is ethnically diverse. Most of the students of this school were Muslim, and the school with proud of Muslim values and identity, as well as its increasing academic competitiveness. The role of civic education teachers in strengthening the importance of religious moderation in MAN Model Manado used the power of curriculum 13 (K-13) and the Nahdlatul Ulama (NU) & Muhammadiyah religious organizations. These two strengths are carried out through an indoctrination teaching strategy, including dichotomy, internalization, and habituation. Their status as State Civil Apparatus (ASN) also influences the strengthening of religious moderation in the learning process. Our research also found that the IPNU (Nahdlatul Ulama Student Association) and the IPM (Muhammadiyah Student Association) base their perceptions on a rational-religious model. In the Manado Model MAN, the position of religious moderation in civics education is more directed to the process of forming public morality rather than class identity hegemony.